Applications for natural deep eutectic solvents in Chinese herbal medicines - Li, Minghui; Rao, Cheng; Ye, Xiaoqian; Wang, Mei; Yang, Boyuan; Wang, Chengxiao; Guo, Liqun; Xiong, Yin; Cui, Xiuming (Frontiers in Pharmacology, 2023)
Chinese herbal medicines (CHMs), with a wide range of bioactive components, are considered to be an important source for new drug discovery. However, the process to isolate and obtain those bioactive components to develop new drugs always consumes a large amount of organic solvents with high toxicity and non-biodegradability. Natural deep eutectic solvents (NADES), a new type of green and designable solvents composed of primary plant-based metabolites, have been used as eco-friendly substitutes for traditional organic solvents in various fields. Due to the advantages of easy preparation, low production cost, low toxicity, and eco-friendliness, NADES have been also applied as extraction solvents, media, and drug delivery agents in CHMs in recent years. Besides, the special properties of NADES have been contributed to elucidating the traditional processing (also named paozhi in Chinese) theory of CHMs, especially processing with honey. In this paper, the development process, preparation, classification, and applications for NADES in CHMs have been reviewed. Prospects in the future applications and challenges have been discussed to better understand the possibilities of the new solvents in the drug development and other uses of CHMs.